Effects of livestock related gender roles on pastoral children and their implication to RVF risk exposure - Mutambo, Irene N.; Bett, Bernard; Bukachi, S.A. (CAB International, 2025)
Background: Children in pastoral communities play a significant role in herding livestock, placing them at a high risk of exposure to zoonotic pathogens such as the Rift Valley fever (RVF) virus. However, socioeconomic studies on knowledge, attitude and practices on RVF often involve adults and community trainings that are usually implemented to bridge knowledge gaps seldom involve children. Understanding how gender roles influence risk exposure is crucial for developing effective prevention strategies.